Can social security programs do more with less? General issues with challenges for southern Africa - Haddad, Lawrence James; Zeller, Manfred (International Food Policy Research Institute, 1997)
There is now a widespread consensus on the importance of social security programs—or more specifically, social welfare programs and safety nets—as a key component of a public policy poverty reduction strategy (World Bank 1990; Graham 1994; van de Walle and Nead 1995). Social security programs are composed of policy and program instruments such as general food subsides, targeted income transfers, public works, school feeding, social funds, small-scale credit, and emergency feeding programs. They are designed to either reduce poverty or prevent poverty, or some combination thereof.